A brief review of affordance in robotic manipulation research. (18th October 2017) - Yamanobe, Natsuki; Wan, Weiwei; Ramirez-Alpizar, Ixchel G.; Petit, Damien; Tsuji, Tokuo; Akizuki, Shuichi; Hashimoto, Manabu; Nagata, Kazuyuki; Harada, Kensuke
Abstract: This paper presents a brief review of affordance research in robotics, with special concentrations on its applications in grasping and manipulation of objects. The concept of affordance could be a key to realize human-like advanced manipulation intelligence. First, we discuss the concept of affordance while associating with the applications in robotics. Then, we intensively explore the studies that utilize affordance for robotic manipulation applications, such as object recognition, grasping, and object manipulation including tool-use. They obtain and use affordance by several ways like learning from human, using simulation, and real-world execution. Moreover, we show our current work, which is a cloud database for advanced manipulation intelligence. The database accumulates various data related to manipulation task execution and will be an open platform to leverage various affordance techniques. Graphical Abstract: